Characterization of Compounds From Extract of Leaf Cloroform Melochia umbellata (Houtt.) Stapf var. Degrabrata K. and Test Antihiperglicemic Activities (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
A research on the characterization of the chloroform extract of leaves of M. umbellata (Houtt.) stapf var. degrabrata K. and activity test as antihyperglycemic has been done. This study aimed to isolate and characterize compounds from chloroform extract and determine the optimum concentration of chloroform extract in  reducing blood glucose levels. Isolation compound from chloroform extract has been done by maceration, fractionation and purification. Based on the data of IR and NMR spectroscopic, compounds isolated from this research were β-sitosterol and fatty acid compound consisting of 25 carbon atoms. The glucose tolerance test, concentration of 6% showed a decrease in glucose levels almost equivalent with drug glibenclamide as comparator.
Keywords: β-sitosterol; Glucose tolerance test; chloroform extract; and Melochia umbellate